The neuroprotective mechanism of dream via ERAD pathway In dyhydroxyphenylglycine preconditioned acute ischemic stroke rats / Nik Nasihah Nik Ramli - Nik Ramli, Nik Nasihah (Institute of Graduate Studies, UiTM, 2017)
Neuroprotective strategies are required to complement the available medical treatments in order to enhance the brain endogenous protective mechanisms and cushion the effect of stroke injury. Pharmacological preconditioning is an avenue of preventative medication anticipated to be highly effective in protecting and reducing the ischemic induced neuronal damage. Recently, in vitro preconditioning studies have shown that prior activation of group I metabotropic receptor (mGluR) with its specific agonist (S)- 3,5-dihydroxyphenylglycine ((S)-3,5-DHPG) elicits neuroprotection against excitotoxicity. Furthermore, the activation of group I mGluR regulates the expression of DREAM. DREAM protein regulates transcription of various genes including edem1 which is a component protein of ER-associated degradation pathway (ERAD). This study elucidates the neuroprotective effect of group I mGluR agonist preconditioning, (S)-3,5-DHPG via DREAM and ERAD in acute ischemic stroke rats. One, 10 or 100 μM (S)- 3,5-DHPG was administered intrathecally to 6 adult male Sprague Dawley rats 2 hours prior to the middle cerebral artery occlusion. After 24 hours, the modified neurological severity score (mNSS) and grid walking test were assessed. The rats were sacrificed and the infarct brain volumes were estimated by 2,3,5-triphenyltetrazolium chloride staining. The serum level of neuron-specific enolase (NSE) and brain tissue level of Bip/GRP78 ER stress marker were assessed by ELISA assays…